PENERAPAN PROSEDUR KESELAMATAN DAN KESEHATAN KERJA PADA PROYEK KONSTRUKSI DINAS PUPR KALIMANTAN TIMUR - Aulia Muttaqin; Benny Mocthar2; Suratmi (Media Bina Ilmiah, 2025)
This study aims to analyzed the implementation of Occupational Safety and Health (OHS) procedure on construction projects in the Public Works, Spatial Planning and Housing Office of East Kalimantan Province, particularly in the Water Resources sector. The focus of this research is on comparing the level of OHS implementation between small and non-small construction companies. The method used in this research was a quantitative approach with questionnaire instruments, validity and reliability tests, and statistical analysis using the Chi-Square test and contingency coefficient. The results showed that there was a difference in the level of implementation of the OHS procedure between small and non-small construction companies, as well as a significant relationship between the company category and the level of compliance with the implementation of OHS. This research can be forms the basis for recommendations to improve the effectiveness of policies, quality of training, implementation of procedures, awareness raising and completeness of work safety facilities.